Theory of Bibliography in Lithuania (Until 1940) - Žukas, Vladas (Knygotyra, 1973)
The development of the theory of bibliography was favoured by the appearance of the important study „Lietuvių bibliografija“ (Lithuanian Bibliography) by V. Biržiška and the course of lectures on bibliography delivered at the University of Kaunas (later transferred to Vilnius).Some observations on bibliography may be found in the prefaces to and reviews of bibliographical publications (V. Biržiška, B. Sruoga, J. Tumas), articles on the history of bibliography (V. Biržiška, I. Kisinas), and the manuscripts of the lectures on bibliography.V. Biržiška had pointed out the following aims of bibliography: to record the facts of printing, to summarize the data of its history and to investigate the relationship between printing and society. B. Sruoga understood these aims in a somewhat broader sense – he emphasized the necessity of studying cultural development and its heritage. J. Tumas and V. Biržiška wrote about two stages of bibliographical research – mere registration and deeper investigation, or historiosophy as J. Tumas put it. Full credit should be given to V. Biržiška for his attempts to define bibliology and to determine its object. He treated bibliology as the science of books and manuscripts in the broadest sense of the word (history, technology of production, artistic design, economical problems of production, etc.). He considered bibliography as a branch of bibliology. B. Sruoga and V. Biržiška were interested in the relationship between the history of literature and bibliography and pointed out the areas of their research. Bibliography, they said, should help the science of literature in presenting the authors fully thus not only serving as a source to the science of literature but also as its supplement. They both appreciated the significance of bibliography in the history of culture. V. Biržiška wrote that concise bibliographical data of the spread of various publications characterize the cultural level of a society or its particular layers, and according to B. Sruoga show the development of national culture and is „the mirror of the cultural maturity of a nation“. B. Sruoga also pointed to the significance of bibliography in the study of the problems of cultural interference. In his articles and manuscripts of lectures V. Biržiška discussed the types of bibliography and the principles of its division as well as the methodological principles of practical work.